INTERNET MARKETING AS AN ELEMENT OF BANKING BUSINESS IN COMPETITIVE ENVIRONMENT - S. L. Orlov; F. M. Minnivaleyev (Russian Journal of Economics and Law)
As any other enterprise, a bank should promote selling of its services, which under the growing competition is possible only on the basis of marketing. Due to the specific character of the banking product, it is clear that under strong competition it is hard to sell a service offered by a definite bank. The new trend in marketing is internet-marketing, which allows to significantly increase the supply of banking products in the market. The article views both the theoretical aspects of bank marketing and the issues of its practical application, and analyzes the new trends in banking internet-marketing.